Simultaneous pH‐sensitive and oxygen‐sensitive MRI of human gliomas at 3 T using multi‐echo amine proton chemical exchange saturation transfer spin‐and‐gradient echo echo‐planar imaging (CEST‐SAGE‐EPI). Issue 5 (6th April 2018) - Harris, Robert J.; Yao, Jingwen; Chakhoyan, Ararat; Raymond, Catalina; Leu, Kevin; Liau, Linda M.; Nghiemphu, Phioanh L.; Lai, Albert; Salamon, Noriko; Pope, Whitney B.; Cloughesy, Timothy F.; Ellingson, Benjamin M.
Abstract : Purpose: To introduce a new pH‐sensitive and oxygen‐sensitive MRI technique using amine proton CEST echo spin‐and‐gradient echo (SAGE) EPI (CEST‐SAGE‐EPI). Methods: pH‐weighting was obtained using CEST estimations of magnetization transfer ratio asymmetry (MTRasym ) at 3 ppm, and oxygen‐weighting was obtained using R 2 ′ measurements. Glutamine concentration, pH, and relaxation rates were varied in phantoms to validate simulations and estimate relaxation rates. The values of MTRasym and R 2 ′ in normal‐appearing white matter, T2 hyperintensity, contrast enhancement, and macroscopic necrosis were measured in 47 gliomas. Results: Simulation and phantom results confirmed an increase in MTRasym with decreasing pH. The CEST‐SAGE‐EPI estimates of R2, R 2 *, and R 2 ′ varied linearly with gadolinium diethylenetriamine penta‐acetic acid concentration (R2 = 6.2 mM −1 ·sec −1 and R 2 * = 6.9 mM −1 ·sec −1 ). The CEST‐SAGE‐EPI and Carr‐Purcell‐Meiboom‐Gill estimates of R2 (R 2 = 0.9943) and multi‐echo gradient‐echo estimates of R 2 * (R2 = 0.9727) were highly correlated. T2 lesions had lower R 2 ′ and higher MTRasym compared with normal‐appearing white matter, suggesting lower hypoxia and high acidity, whereas contrast‐enhancement tumor regions had elevated R 2 ′ and MTRasym, indicating high hypoxia and acidity. Conclusion: The CEST‐SAGE‐EPI technique provides simultaneous pH‐sensitive and oxygen‐sensitive image contrasts for evaluation of the brain tumor microenvironment. Advantages include fast whole‐brain acquisition, in‐line B0 correction, and simultaneous estimation of CEST effects, R2, R 2 *, and R 2 ′ at 3 T.